Confined space airway management: a narrative review - Soren S. Rudolph; Christopher W. Root; Michael Friis Tvede; Trond Fedog; Patrick Wenger; Mikael Gellerfors; Jelsche Apel; Luca Ünlü (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Airway management is a critical component of prehospital and emergency care, often complicated by the environment in which it is performed. Confined space airway management (CSAM) refers to scenarios were restricted physical space challenges conventional airway techniques. These situations may occur in unpredictable environments, such as vehicle entrapments or collapsed structures, and controlled settings like helicopters. This narrative review aims to synthesize current knowledge, expert opinions, and evidence on CSAM. Main body CSAM poses logistical and technical challenges, including limited access to the patient, restricted movement, and reduced visibility. These factors increase the difficulty of performing standard airway management procedures and increase the risk of complications. Supraglottic airways (SGA), due to their ease of insertion and high success rates, are recommended as a first-line approach in CSAM, especially when intubation is delayed or infeasible. Tracheal intubation (TI) may require significant modifications in technique. Alternative methods and adjuncts such as face-to-face intubation and stylets may be considered but are highly dependent on provider expertise and the specific scenario. Emergency front of neck access (eFONA) is provided with high success rated in confined spaces. In controlled settings, systematic preparation can improve success rates and reduce procedural times. In uncontrolled environments, prioritizing patient extrication and maintaining oxygenation is essential, as definitive airway management may conflict with rescue efforts. Conclusion CSAM requires a strategic blend of medical expertise, adaptive techniques, and logistical planning. A focus on training, preparedness, and the use of supraglottic airway devices may mitigate challenges in these high-stakes scenarios.